2001
DOI: 10.1165/ajrcmb.24.6.4301
|View full text |Cite
|
Sign up to set email alerts
|

Eotaxin-3 but Not Eotaxin Gene Expression Is Upregulated in Asthmatics 24 Hours after Allergen Challenge

Abstract: Eotaxin is an important mediator of eosinophil recruitment and activation in the airways of asthmatics. Eotaxin-2 and eotaxin-3 are two recently identified chemokines with activity similar to that of eotaxin. Using quantitative polymerase chain reaction analysis, we determined the messenger RNA (mRNA) expression of eotaxin, eotaxin-2, and eotaxin-3 relative to GAPDH mRNA expression in bronchial biopsies and bronchoalveolar lavage fluid (BALF) cells obtained from subjects with mild asthma, asthmatic subjects 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
89
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 27 publications
2
89
1
1
Order By: Relevance
“…Our immunohistochemistry results of increased eotaxin-3 expression in the nasal epithelium of allergic human subjects extends our in vitro studies to the in vivo setting, and are consistent with studies by Berkman et al [29] and Komiya et al [23] in asthmatic subjects. Berkman and colleagues found that eotaxin-3 was markedly up-regulated in patients with asthma 24 h after allergen challenge as demonstrated by PCR analysis of bronchial biopsies [29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our immunohistochemistry results of increased eotaxin-3 expression in the nasal epithelium of allergic human subjects extends our in vitro studies to the in vivo setting, and are consistent with studies by Berkman et al [29] and Komiya et al [23] in asthmatic subjects. Berkman and colleagues found that eotaxin-3 was markedly up-regulated in patients with asthma 24 h after allergen challenge as demonstrated by PCR analysis of bronchial biopsies [29].…”
Section: Discussionsupporting
confidence: 91%
“…Berkman and colleagues found that eotaxin-3 was markedly up-regulated in patients with asthma 24 h after allergen challenge as demonstrated by PCR analysis of bronchial biopsies [29]. Using immunohistochemistry, Komiya and colleagues demonstrated eotaxin-3 staining in bronchial epithelium isolated from asthmatic patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the chemokine receptor CCR3 is expressed on cells implicated in the pathogenesis of allergic inflammation, such as eosinophils, basophils, mast cells and Th2-type T lymphocytes [14][15][16][17]. The major CCR3 ligands are the eotaxin family of CC chemokines, CCL11/eotaxin [18,19], CCL24/eotaxin-2 [20][21][22] and CCL26/eotaxin-3 [23,24], which share low aminoacid sequence identity and are characterized by differences in their potencies and efficacies at CCR3 as well as distinct temporal and spatial expression patterns [21,[24][25][26][27]. In has been suggested that leukocyte recruitment during inflammatory responses may be tightly regulated by chemokines acting as agonists at some receptors and antagonists at others.…”
Section: Introductionmentioning
confidence: 99%
“…CCR3-activating ␤-chemokines are elevated in human asthmatics (14 -16) and are markedly up-regulated upon allergen challenge in animal models (5,(17)(18)(19)(20)(21) and in humans (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%